PENERAPAN MEDIA AUDIO VISUAL SEBAGAI UPAYA MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI KELAS VII MTSS YASTI PIMPINAN TAHUN PELAJARAN 2023-2024 - Hapinas Hapinas; Aslan Aslan; Mauizatul Hasanah (ADISAM PUBLISHER, 2025)
This research aims to find out and obtain information about: 1) The application of audio visual media in the Aqidah Akhlak learning process in class VII MTs Yasti Leadership for the 2023-2024 academic year and the extent to which it is effective in increasing students' interest in learning, 2) Factors that influence success application of audio visual media in increasing students' interest in learning in the Aqidah Akhlak subject in class VII MTs Yasti Leadership for the 2023-2024 academic year. This research uses a qualitative approach with a phenomenological type of research. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data presentation and conclusions. The data validity techniques used are source triangulation and member checking. The results of this research indicate that: (1) the application of audio-visual media in the Aqidah Akhlak learning process is the availability of devices and media such as projectors, computers, televisions, and audio speakers which are the main tools that must be available and function well, the quality of audio-visual media with image resolution and graphic clarity are adequate, integration in the curriculum helps students understand the material better because it involves more senses, (2) factors that influence the success of implementing audio-visual media in increasing students' interest in learning in the subject of Aqidah Akhlak are the quality of the media audio visual, presentation method, readiness and teacher competency, availability of audio visual devices, students' basic ability to use the required technology, learning environment, evaluation and feedback